Characteristics of the Superficial Circumflex Iliac Artery Perforator Flap in a Western Population and a Practice Approach for Free Flap Reconstruction - Messa, Charles A., IV; Carney, Martin J., III; Tantillo, Kristopher; Othman, Sammy; Moores, Craig; Mirzabeigi, Michael N.; Weissler, Jason M.; Cook, Tessa; Kovach, Stephen J. (Journal of Reconstructive Microsurgery, 2020)
Background There has been increasing interest in the superficial circumflex iliac artery perforator (SCIP) flap as a source of thin, pliable soft tissue combined with a favorable donor site. Despite several clinical series from Asia, barriers to adoption include reluctance to perform submillimeter “supermicrosurgery” and the effect of body habitus on flap feasibility. The purpose of this study is to distinguish vascular anatomic characteristics of the SCIP flap in a North American population.Methods Computed tomography angiography was examined in 84 flaps in healthy prospective renal donor patients from a radiographic database. Descriptive statistics as well as linear regression comparing variables to body mass index (BMI) were performed.Results Mean BMI was 27.1 ± 3.5 kg/m2, while the mean patient age was 47.8 ± 11.4 years. The superficial circumflex iliac artery (SCIA) originated from the common femoral artery in 92% cases, with remainder originating from the profunda femoris. The mean vessel diameter was 1.85 mm at source vessel origin. Distance from skin to source vessel averaged 30.7 mm. Suprascarpal subcutaneous thickness averaged 16.5 mm. The mean distance from Scarpa's fascia to vessel origin was 14.1 mm. Direct three-dimensional distance from vessel origin to pubic tubercle was 50.2 mm. A medial and lateral perforator split off of the SCIA was observed in 38 cases (45%). Significant differences were shown when comparing BMI to skin to source vessel distance (p < 0.001), suprascarpal subcutaneous fat thickness (p < 0.001), and fascial distance to vessel origin (p < 0.001). BMI did not significantly affect vessel diameter.Conclusion Despite a significantly higher BMI than many previously published cohorts, the SCIP remains an excellent source of thin and pliable tissue. When dissected closer to the source vessel, a vessel caliber of nearly 2 mm can be achieved, which may obviate the need for “supermicrosurgery” in this population.
Keywords: superficial circumflex iliac artery flap; SCIP; microsurgery; supermicrosurgery; perforator flap